Myocardial Ischemia Caused by Subepicardial Hematoma - Grieshaber, Philippe; Nef, Holger; Böning, Andreas; Niemann, Bernd (The Thoracic and Cardiovascular Surgeon Reports, 2017)
Background Bleeding from bypass anastomosis leakage occurs early after coronary artery bypass grafting. Later, once the anastomosis is covered by intima, spontaneous bleeding is unlikely.Case Description A 63-year-old male patient developed a pseudoaneurysm-like, subepicardial late-term bleeding resulting in a hematoma that compromised coronary artery flow by increasing extracoronary pressure. This resulted in severe angina pectoris (Canadian Cardiovascular Society IV) and myocardial ischemia within the affected area. After surgical removal of the hematoma and repair of the anastomosis, the patient's symptoms disappeared and no signs of myocardial ischemia were present.Conclusion Surgical removal is an efficient therapy for subepicardial hematoma inducing myocardial ischemia.
Keywords: complication; myocardial ischemia; hematoma; coronary artery bypass grafting; CABG